PENGARUH MOTIVASI, TUNJANGAN KINERJA DAN KOMITMEN PIMPINAN TERHADAP TINGKAT KECURANGAN PEGAWAI - Qodari, Amimah; Fachruzzaman, Fachruzzaman; Coryanata, Isma (JURNAL FAIRNESS, 2018)
The aim of this research is to investigate the effect of motivation, performance allowance, and leaders’ commitment toward employees’ fraud level at Institut Agama Islam Negeri (IAIN) Curup. The population of this research is all 50 civil servants of IAIN Curup who receive performance allowance. This research employs total sampling method in which the sample is the whole number of population. The result shows that motivation positively affects the employees’ fraud level. On the other hand, performance allowance negatively affects the employees’ fraud level, and the leaders’ commitment does not give any effect to the employees’ fraud level.